Pengaruh Pemberian Jus Belimbing Wuluh (Averrhoa Bilimbi L) terhadap Penurunan Kadar Kolesterol pada Penderita Kolesterol di Wilayah Kerja Puskesmas Kabawo Kabupaten Muna Tahun 2022 - Salwan, Salwan; Hasrima, Hasrima; Herman, Herman (Jurnal Gizi Ilmiah, 2022)
Hypercholesterolemia is a condition of elevated cholesterol levels in the blood that exceeds the normal limit, which is 240 mg / dl. Hypercholesterolemia cano beotreatedbwith pharmacologicalnandnnon-pharmacologicalnntherapies. Pharmacologicalm therapy of hypercholesterolemia can be carried out by taking cholesterol-lowering drugs. However, taking cholesterol-lowering drugs in the long term can cause adverse effects on the body, which can aggravate the work of the kidneys, myopathy, liver damage, and kidney failure. So that non-pharmacological therapy or traditional medicine is needed in reducing cholesterol levels, one of which is by consuming star fruit juice. This study aims to determine the effect of star fruit juice on decreasing cholesterol levels in hypercholesterolemia patients. The design used in this study is aopre-experimentalmdesign. By using the onengroupnpretestlposttestmapproach. The results of the statistical test using the Paired T Test obtained a p value of 0.000 (sig > 0.050) meaningnthatnHIi waslaccepted and H0 was rejected. In conclusion, there is an influence of star fruit juice on reducing cholesterol levels in hypercholesterolemia patients in the Kabawo Health Center Working Area, Muna Regency. Advice is expected for health workers to apply non-pharmacological therapy, especially the use ofo sta fruitojuice as aodecrease inm cholesterol levels in people with hypercholesterolemia